PENGARUH BAHAN FIKSASI TERHADAP INTENSITAS WARNA DAN KETAHANAN LUNTUR PEWARNAAN KULIT CRUST IKAN PARI DENGAN PEWARNA SECANG (Caesalpinia sappan L) - Entin Darmawati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
Research objective is to now determine the effect of different fixation materials and dye concentration secang ( Caesalpinia sappan L ) Pari crust on the skin of the fish ( Dasyatis Khulii ) dye method to color intensity and fastness . Research coloring process secang on crust leather stingray with the Immersion Method Material Variation fixation (tawas, tunjung ) concentration (3%,6%,9%) b/v, the concentration of dyes cup (5 % , 10 % , 15 % w / v ), immersion time ( 60 minutes , 90 minutes , 120 minutes ) , the intensity of the color and fastness. Analysis of the data using the program Variant Analysis ( Anova ) classification 3 lanes. Results The color intensity and fastness test on crust leather stingray no difference to a dry rub to demonstrate the value of SS ( Stainning Scale ) of 4.0 ( good ) on secang concentration of 5 % w / v , staining time of 120 minutes and fixation Tunjung ( 6 % ) , the intensity of the color is darker ., A value of 4.5 ( good ) on the fixation of lotus 6 % % w / v , concentration secang 10 % w / v , staining time of 120 minutes . Fixation alum 6 % . SS value = 4.5 ( good ) , secang concentration of 10% , the intensity of a lighter color . It can be concluded that the intensity of the color indicates that the fixation material is able to bind more strongly lotus leave a blue-red color of the material fixation alum gives pink and test results of color fastness to rubbing lotus stronger than alum the higher the concentration of fixation , then the better the erosion resistance.